The effect of education based on based health belief model on osteoporosis and bone mineral density among women - Ali Khani Jeihooni; Seyyed Mansour Kashfi; Zahra Khiyali; Hassan Jamshidi; Seyyed Hannan Kashfi (Gonabad University of Medical Sciences, 2019)
Osteoporosis is a systemic skeletal disorder characterized by reduction of one mass, deterioration of bone structure, increase of bone fragility, and fracture risk increment. The purpose of this study was to investigate the effect of an educational program based on Health Melief Model (HBM) onosteoporosis and Bone Mineral Density (BMD) in women. In this quasi-experimental study, 160 participants registered with the health centers. 80 participants were randomly divided into the experimental and control groups. In order to measure the efficacy of nutrition and walking performance for prevention of osteoporosis, a questionnaire consisting of demographic information and HBM constructs was used before, immediately after the intervention, and 12 months following the intervention. BMD was recorded at the lumbar spine and femur before and 12 months following the intervention. Compared to the control group,the experimental group showed a significant increase in their knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, internal cues to action, nutrition, and walking performance immediately and one year after the intervention. Twelve months following the intervention, the value of lumbar spine and hip BMD T-Score in the experimental group increased, while in the control group it reduced. This study revealed the effect of knowledge, walking, and diet on bone mass based on HBM model. Hence, these models can act as a framework for designing and implementing educational interventions in order to prevent osteoporosis.